Uma abordagem sobre os desvios de função no magistério público municipal de Cachoeira do Sul - Santos Júnior, Sérgio Augusto Ramos dos (2021)
This work is the result of a master's research that has as main objective to identify the impact of the cost of the municipal teacher, in deviation of function, for the city hall of Cachoeira do Sul, in the period from 2010 to 2020. The perceptions about management of people in education and the costs of this policy, the specifications of education and educators, as well as the characteristics of the municipal public teaching. The methodology was an exploratory research and case study, with a qualitative and quantitative approach, as a data collection instrument the semi-structured interview with municipal managers of Administration, Education, Finance and the head of Internal Control of the municipality of Cachoeira do Sul, questionnaire on -line with teachers from the municipal network and documentary research, between the years 2010 to 2020. In addition, the ethical dimensions, the timetable and the data collection tool were presented. Teachers are the most qualified civil servants, due to the training and qualification requirements, there are financing laws to guarantee the effectiveness of this policy, which will impact the expenditure, in addition to the number of teachers on duty, who are paid from the single cashier from the city hall and are usually the most expensive for their training. Teachers feel devalued by management and by the community of Cachoeirense, in addition to the picture of many teachers on sick leave, interests, better pay, among other factors. It was concluded that there is an impact of the cost of the municipal teacher, in a deviation of function, for the city of Cachoeira do Sul, in the period from 2010 to 2020 and the proposed contributions to maximize possible impacts for the management, even this trend with signs of reduction.